2004
DOI: 10.1038/oby.2004.124
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Commercial Internet Weight Loss Program

Abstract: EWING. A randomized controlled trial of a commercial Internet weight loss program. Obes Res. 2004;12: 1011-1018. Objective: To assess, in a 1-year randomized controlled trial, the efficacy of eDiets.com (a commercial Internet weight loss program) in improving weight, cardiovascular health, and quality of life. Research Methods and Procedures: Participants were 47 women with a mean age of 43.7 Ϯ 10.2 (SD) years and a mean BMI of 33.5 Ϯ 3.1 kg/m 2 . They were randomly assigned to either: 1) eDiets.com, a commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
247
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(260 citation statements)
references
References 27 publications
10
247
3
Order By: Relevance
“…This is in keeping with earlier studies (with larger samples) suggesting that individuals in weight loss treatments enhanced with MI lose more weight than those in treatments without MI (e.g., . Although it is difficult to compare across studies due to differences in samples and methodology, the weight losses experienced by women in the GSH/MI group over 3 months were comparable to those reported in Womble et al's (2004) This suggests that the LEARN manual might be most effective in a shorter-term, MIenhanced format.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This is in keeping with earlier studies (with larger samples) suggesting that individuals in weight loss treatments enhanced with MI lose more weight than those in treatments without MI (e.g., . Although it is difficult to compare across studies due to differences in samples and methodology, the weight losses experienced by women in the GSH/MI group over 3 months were comparable to those reported in Womble et al's (2004) This suggests that the LEARN manual might be most effective in a shorter-term, MIenhanced format.…”
Section: Discussionmentioning
confidence: 65%
“…Both Womble et al (2004) and Gardner et al (2007) reported mean weight losses at a one-year follow-up. In the Womble et al (2004) study, the LEARN group lost 4 kg (8.82 lbs.).…”
Section: This Represents a Clinically Significant Weight Loss (Nhlbi mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have examined the use of online social networks, including online group chats and message board, primarily to connect participants outside of in-person meetings [16,17]. Two recent systematic reviews indicated that online social networks have been primarily used as an adjunct to in-person or web-based weight loss interventions, rather than as the primary treatment modality [18,19].…”
Section: Introductionmentioning
confidence: 99%